Condensin I binds chromatin early in prophase and displays a highly dynamic association with Drosophila mitotic chromosomes. - Oliveira, R.A.; Heidmann, S.; Sunkel, C.E. (Chromosoma, 2007)
The condensed state of mitotic chromosomes is crucial for faithful genome segregation. Key factors implicated in the formation of mitotic chromosomes are the condensin I and II complexes. In Drosophila, condensin I appears to play a major role in mitotic chromosome organization. To analyze its dynamic behavior, we expressed Barren, a condensin I non-Structural Maintenance of Chromosomes subunit, as a fully functional enhanced green fluorescent protein (EGFP) fusion protein in the female and followed it during early embryonic divisions. We find that, in Drosophila, Barren-EGFP associates with chromatin early in prophase concomitantly with the initiation of chromosome condensation. Barren-EGFP loading starts at the centromeric region from where it spreads distally reaching maximum accumulation at metaphase/early anaphase. Fluorescence Recovery After Photobleaching analysis indicates that most of the bound protein exchanges rapidly with the cytoplasmic pool during prometaphase/metaphase. Taken together, our results suggest that in Drosophila, condensin I is involved in the initial stages of chromosome condensation. Furthermore, the rapid turnover of Barren-EGFP indicates that the mechanism by which condensin I promotes mitotic chromosome organization is inconsistent with a static scaffold model.